Engagement in Internet Language-Related Activities and Grammatical Proficiency of Grade 11 Students - Apurado, Mark Anthony M.; Legaspi, Ma. Judy B. (Philippine Social Science Journal, 2020)
English, being the language needed in today’s modern world, is seen and encountered in everyday lives. Humankind needs to understand and be understood by one another. This undertaking played around the assumption that internet use affects the grammatical proficiency of students. The dependence and frequency of internet use have become quite a concern to both parents and teachers because both cannot control how and why students access the internet. Given the wide literature gap, this descriptive, comparative, and correlational study determined the extent of engagement in internet language-related activities of Grade 11 students. Furthermore, it examined the difference in the level of grammatical proficiency of Grade 11 students when grouped according to the program. Lastly, this paper examined the relationship between engagement in internet language-related activities and grammatical proficiency.